Prognostic Value of a Novel Signature With Nine Hepatitis C Virus-Induced Genes in Hepatic Cancer by Mining GEO and TCGA Databases - Wei, Jianming; Wang, Bo; Gao, Xibo; Sun, Daqing (Frontiers in Cell and Developmental Biology, 2021)
Background: Hepatitis C virus-induced genes play a critical role in regulating tumor development in hepatic cancer. The role of hepatitis C virus-induced genes (HCVIGs) in hepatic cancer remains unknown. This study aimed to construct a prognostic signature and assess the value of the risk model for predicting the prognosis of hepatic cancer. Methods: Differentially expressed HCVIGs were identiﬁed in hepatic cancer data from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases using library ("limma") package of R software. The protein-protein interaction (PPI) network was constructed using the Cytoscape software. Functional enrichment analysis was performed using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Univariate and multivariate Cox proportional hazard regression analyses were applied to screen for prognostic HCVIGs. The signature of HCVIGs was constructed. Gene set enrichment analysis (GSEA) compared low-risk and high-risk groups. Finally, the International Cancer Genome Consortium (ICGC) database was used to validate this prognostic signature. Polymerase chain reaction (PCR) was performed to validate the expression of nine HCVIGs in the hepatic cancer cell lines. Results: A total of 143 differentially expressed HCVIGs were identified in the TCGA hepatic cancer dataset. Functional enrichment analysis showed that DNA replication was associated with the development of hepatic cancer. The risk score signature was constructed based on the expression of ZIC2, SLC7A11, PSRC1, TMEM106C, TRAIP, DTYMK, FAM72D, TRIP13, and CENPM. In this study, the risk score was an independent prognostic factor in the multivariate Cox regression analysis (HR=1.433, 95% CI=1.280–1.605, P<0.001). The overall survival curve revealed that the high-risk group had a poor prognosis. The Kaplan-Meier Plotter online database showed that the survival time of hepatic cancer patients with overexpression of HCVIGs in this signature was significantly shorter. The prognostic signature-associated GO and KEGG pathways were significantly enriched in risk group. This prognostic signature was validated using external data from the ICGC databases. The expression of nine prognostic genes were validated in HepG2 and LO-2. Conclusion: This study evaluates a potential prognostic signature and provides a way to explore the mechanism of HCVIGs in hepatic cancer.